A service-learning program assessment: Strengths, weaknesses and impacts on students - Rocío Samino García (Intangible Capital, 2023)
Purpose: This paper aims to research the strengths and weaknesses of service-learning programs in order to identify the challenges of their application, the educational possibilities of service-learning and the impact on students. Design/methodology/approach: An observational case study model was used, through a qualitative research approach based on participant observation. Additional data collection tools were used before and after the service-learning methodology; these included personal interviews, field diaries and videos. Data analysis was performed using Atlas.ti7 qualitative software. Findings: This paper shows the relevant educational possibilities of service-learning. Students have the potential to take action in response to social problems, using the professional skills they have learned in their degree program, encouraging their critical awareness through reflection processes and promoting their involvement as citizens engaged in their own reality. This work reveals both the strengths and weaknesses of service-learning programs, including the needs assessment, project-based learning, and partnership engagement, all of which are outlined as challenges in terms of their application. Research limitations: The findings of this qualitative paper pertain to one single case, but they are generalizable to related theories. Practical implications: This research could be used to a guide to begin or improve service-learning projects in higher education. Social implications: The findings on the social impact of service-learning for all the agents involved show the positive value of service-learning. Moreover, it shows service-learning is an efficient tool to introduce sustainability and the SDGs in the students’ curriculum. Originality/value: this research reveals the importance of the promotion and evaluation of service-learning in an area where little research has been done in this regard.